Development of a static wall testing apparatus configured for testing joint sealants against water intrusion - Lindo, Kristine Faye DC
In the Philippines, precast concrete technology is a rapidly developing construction method geared towards achieving construction efficiency in terms of construction cost, quality and time. However, this said technology inherently increases the number of joints in wall systems which are locations highly susceptible to water intrusion in cases of sealant deterioration or failure. This study aims at developing an accessible apparatus with testing parameters and protocols for assessing the performance of vertical joint sealants against water intrusion. The result of this research endeavor is an operational and accessible testing apparatus with capacities comparable to those standards and assemblies found abroad while retaining flexibility to accommodate local testing parameters. In commissioning of the apparatus, a total of 12 set-ups were implemented, the flow rate of 4 L/min and the crack length of 16 mm were held constant while varying the air pressure (0 Pa, 500 Pa, 1000 Pa and 1500 Pa) and the displacement (0 mm, 1 mm and 2mm) of the sealant. The results exhibited the same trend compared with values obtained from a similar study conducted by Lacasse et. al in 2009 in Institute for Research in Construction, National Research Council Canada in Ottawa.